Comprehensive mutation detection of BRCA1/2 genes reveals large genomic rearrangements contribute to hereditary breast and ovarian cancer in Chinese women - Wen-Ming Cao; Ya-Bing Zheng; Yun Gao; Xiao-Wen Ding; Yan Sun; Yuan Huang; Cai-Jin Lou; Zhi-Wen Pan; Guang Peng; Xiao-Jia Wang (BMC Cancer, 2019)
Abstract Background Mutated BRCA1/2 genes are associated with hereditary breast and ovarian cancer (HBOC). So far most of the identified BRCA1/2 pathogenic variants are single nucleotide variants (SNVs) or insertions/deletions (Indels). However, large genomic rearrangements (LGRs) such as copy number variants (CNVs) are also playing an important role in HBOC predisposition. Their frequency and spectrum have been well studied in western populations but remain largely unknown for Chinese population. Methods Peripheral blood samples were collected from 218 unrelated familial breast and/or ovarian cancer (FBOC) patients living in Eastern China. PCR-based Sanger sequencing and panel-based next-generation sequencing (NGS) were performed to detect pathogenic SNVs and Indels in BRCA1/2 genes. For the patients lacking small pathogenic variants, multiplex ligation dependent probe amplification (MLPA) assay was conducted to screen for LGRs. Results In total, we identified 44 samples (20.1%) carrying small pathogenic variants (26 in BRCA1 and 18 in BRCA2, respectively). Among the rest of 174 samples, five were found carrying novel deleterious LGRs in BRCA1 which are exon5-7dup (1 patient), exon13-14dup (2 patients), and exon1-22del (2 patients). No LGR was found in BRCA2. Overall, LGRs accounted for 16.1% (5/31) of BRCA1 pathogenic variants, and were detected in 2.3% (5/218) of all FBOC patients., Conclusions LGR variants in BRCA1 gene play a significant role in Chinese HBOC patients. MLPA or other similar LGR-detecting methods should be recommended along with nucleotide sequencing as the initial screening approach for Chinese HBOC women.